BURNOUT DI KALANGAN PENDAKWAH - Nadiatus Salama (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2014)
Burnout is a phenomenon that arose from a great expectation to do the best for other people. But when the relationship is